Robust nonparametric statistical methods - Hettmansperger, Thomas P., 1939-; McKean, Joseph W., 1944- (Boca Raton, Fla. : CRC Press, 2011)
"Often referred to as distribution-free methods, nonparametric methods do not rely on assumptions that the data are drawn from a given probability distribution. With an emphasis on Wilcoxon rank methods that enable a unified approach to data analysis, this book presents a unique overview of robust nonparametric statistical methods. Drawing on examples from various disciplines, the relevant R code for these examples, as well as numerous exercises for self-study, the text covers location models, regression models, designed experiments, and multivariate methods. This edition features a new chapter on cluster correlated data"--
1. One-sample problems -- 2. Two-sample problems -- 3. Linear models -- 4. Experimental designs : fixed effects -- 5. Models with dependent error structure -- 6. Multivariate.
Includes bibliographical references (p. 495-520) and indexes.
"A Chapman & Hall book."
Also available as an electronic resource.
Keywords: Nonparametric statistics; Robust statistics